Kant's political theory : interpretations and applications - Ellis, Elisabeth (Pennsylvania State University Press, 2012)
"A collection of essays examining Immanuel Kant's lectures and minor writings as well as his political essays. Offers a comprehensive introduction to Kant's political thought from a position of engagement with modern political and philosophical questions"--Provided by publisher
Keywords: Kant, Immanuel, -- 1724-1804 -- Political and social views.; Kant, Immanuel, -- 1724-1804; Kant, Immanuel -- 1724-1804; PHILOSOPHY -- Political.; POLITICAL SCIENCE -- History & Theory.; Political and social views; Politische Philosophie; Political Science.; Law, Politics & Government.; Political Theory of the State.